Phytochemical screening and in vitro antioxidant activity of Psidium guajava - Venkatachalam, Ravi Narayan; Singh, Kanchanlata; Marar, Thankamani (Free Radicals and Antioxidants)
Free radicals or Reactive oxygen species (ROS), a class of highly reactive molecules derived from the metabolism of oxygen is believed to be involved in many health disorders. ROS including superoxide radicals, hydroxyl radical and hydrogen peroxide molecules are often generated as by products of biological reactions or from exogenous factors. Antioxidant-based drugs and formulations for the prevention and treatment of complex diseases have attracted a great deal of research interest in natural antioxidants. It is necessary to screen medicinal plants for their antioxidant potential. Determination of phytochemical constituents like phenols, flavonoids, tannins, chlorophyll and carotenoids and various tests like reducing power, ferric reducing antioxidant power, linoleic acid assay, DPPH, nitric oxide, superoxide and hydrogen peroxide radical scavenging assays for evaluation of in vitro antioxidant activity of methanolic and aqueous extracts of Psidium guajava (Guava) leaves were carried out. It was found that the methanolic extracts showed greater amount of phytochemicals and higher antioxidant activity than aqueous extracts. Present results indicate that guava is a good candidate for development of new nutraceuticals for treatment of diseases like diabetes. However, in vivo studies to determine the antioxidant potential of the plant should be conducted before they can be recommended as nutritional substitutes.
Keywords: flavanoids; phenols; DPPH; oxidative stress; reactive oxygen species; guava